Critical care nursing : a holistic approach - Morton, Patricia Gonce; Fontaine, Dorrie K. (Philadelphia : Wolters Kluwer, 2017)
"Focusing on preparing students to provide optimal care for critically ill patients and their families, this updated 11th Edition of Morton's classic text integrates the latest research in health care and nursing education, while providing clear, concise writing; outstanding photographs and illustrations; and a holistic approach to the complexities of critical care nursing. By presenting theory and principles within the context of practical application, the authors promote critical thinking and clinical decision-making in every chapter and emphasize the patient as the center of the health care team's efforts"--Publisher's description
Part 1: The concept of holism applied to critical care nursing practice. Critical care nursing practice: promoting excellence through caring, collaboration, and evidence -- The patient's experience with critical illness -- The family's experience with critical illness -- Patient and family education in critical care -- Relieving pain and providing comfort -- Palliative care and end-of-life issues in critical care -- Part 2: Professional practice issues in critical care. Ethical issues in critical care nursing -- Legal issues in critical care nursing -- Building a professional practice model for excellence in critical care nursing -- Part 3: Special populations in critical care. The critically ill pediatric patient -- The critically ill pregnant woman -- The critically ill older patient -- The postanesthesia patient -- Part 4: Special situations in critical care. Rapid response teams and transport of the critically ill patient -- Disaster management: implications for the critical care nurse -- Part 5: Cardiovascular system. Anatomy and physiology of the cardiovascular system -- Patient assessment: cardiovascular system -- Patient management: cardiovascular system -- Common cardiovascular disorders -- Heart failure -- Acute myocardial infarction -- Cardiac surgery -- Part 6: Respiratory System. Anatomy and Physiology of the Respiratory System -- Patient Assessment: Respiratory System -- Patient Management: Respiratory System -- Common Respiratory Disorders -- Acute Respiratory Distress Syndrome -- Part 7: Renal system. Anatomy and physiology of the renal system -- Patient assessment: renal system -- Patient management: renal system -- Acute kidney injury and chronic kidney disease -- Part 8: Nervous system. Anatomy and physiology of the nervous system -- Patient assessment: nervous system -- Patient management: nervous system -- Common neurosurgical and neurological disorders -- Traumatic brain injury -- Spinal cord injury -- Part 9: Gastrointestinal system. Anatomy and physiology of the gastrointestinal system -- Patient assessment: gastrointestinal system -- Patient management: gastrointestinal system -- Common gastrointestinal disorders -- Part 10: Endocrine system. Anatomy and physiology of the endocrine system -- Patient assessment: endocrine system -- Common endocrine disorders -- Part 11: Hematological and immune systems. Anatomy and physiology of the hematological and immune systems -- Patient assessment: hematological and immune systems -- Organ and hematopoietic stem cell transplantation -- Common immunological disorders -- Common hematological disorders -- Part 12: Integumentary system. Anatomy and physiology of the integumentary system -- Patient assessment: integumentary system -- Patient management: integumentary system -- Burns and common integumentary disorders -- Part 13: Multisystem dysfunction. Shock, systemic inflammatory response syndrome, and multiple organ dysfunction syndrome -- Trauma -- Drug overdose and poisoning
Includes bibliographical references and index
Keywords: Intensive care nursing; Holistic nursing; Critical Care; Holistic Nursing